PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) DI KELAS VC SD NEGERI 47 KOTA JAMBI - Dewi Sutria (Jurnal Pesona Dasar, 2019)
The purpose of this study are to increase students’ learning activities in the learning process of mathematics by applying the type of Think-Pair-Share (TPS) cooperative learning and to improve students’ learning outcomes in mathematics. This research was carried out in the fifth grade Students in Elemntary School 47 Jambi  during the first semester of 2017/2018 Academic Year. The action was carried out in 2 cycles with the subject matter covered in cycle I was about explaining and reducing two fractions with different denominators and in cycle II about multiplication and division of decimal fractions. Data was collected by observation methods using observation sheets and student learning outcomes was collected using tests. The results of the study based on data analysis showed an increase in learning outcomes from 64.29% wich is sufficient category in the first cycle to be a good category in the second cycle with 83.93%. For student learning outcome there was an improvement from 50% with inactive categories to 90% with very active categories.. The results of this study indicate that the application of the Think-Pair-Share (TPS) Cooperative Learning model can be used to improve student learning outcomes.